Community Knowledge and Attitude to Conduct Covid-19 Booster Vaccination - Rahmadyanti Rahmadyanti; Masruloh Masruloh (STIKep PPNI Jawa Barat, 2022)
Aims: This study aimed to identified the knowledge and attitude related to COVID-19 booster vaccination among community. Methods: This Research used a cross sectional design. The sampling technique was purposive sampling on 101 samples in Jatinegara District, East Jakarta which was carried out from January 2022 to February 2022 using a google form questionnaire. Presentation of data with descriptive analysis and chi square test. Results: Characteristics of respondents related to the attitude of the community to carry out COVID-19 booster vaccinations in Jatinegara sub-district, the majority are in the age range of 29 years, namely 53.5%, low education 61.4% and not working 54.5%. There is a significant relationship between motivation and attitude with a p-value of 0.000 Conclusion: The motivation variable has a significant relationship with people's attitudes in carrying out COVID-19 booster vaccinations.